Dampak Penggunaan Gadget Terhadap Kesehatan Mata Remaja - Alisyahbana, Adam Trojan (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
The use of gadgets covers every age group of society, including children, teenagers, adults and the elderly. Of each of these groups, the percentage of gadget users among teenagers is the largest, namely 98.20%, which means that almost all teenagers in Indonesia use gadgets in their daily lives. Excessive use of gadgets will have a negative impact on teenagers, one of which is a decrease in eye health caused by staring at gadget screens too often. This research aims to examine the results of Indonesian language research on the impact of gadget use on adolescent eye health. The method used in this research is a literature review, where the literature search was carried out via Google Scholar. The keywords used in Indonesian are